Slave Trade Syndicates: Contestation of Slavery in Timor between Local Rulers, Europeans, and Pirates in the 19th century - Fanada Sholihah; Yety Rochwulaningsih; Singgih Tri Sulistiyono (Journal of Maritime Studies and National Integration, 2019)
This article analyses the contestation of slavery activities in Timor during 19th  century. The slave trade cannot be separated from contestation between three forces, namely the local authority (rajah), colonial entities residing in Timor, and pirates from Bugis, Ende, and Sulu.  The rajah fought each other on the battlefield to decide which of them worthy of a “gift” of the war, which were women and children as merchandise for sale. Meanwhile, colonial complaints about the limited human labor to be employed in various types of work not only encouraged increased slave raiding and the purchase of slaves in distant places, but at the same time fostered slave trading activities, both were sponsored by the Dutch and Portuguese. One of the main causes of the ongoing slave trade was piracy at sea, three actors were pioneering slave raiding, namely Balanini/Ilanun, Bugis and Makassar pirate, and Ende pirate. By applying historical method, this research questioned why locals, Europeans, and pirate rulers contested to obtain slaves in Timor? The rise of capitalism was marked by the demand for cheap labor in 19th century. Therefore, slave commodities were mobilized to meet the need for labour in plantations or companies owned by the colonial government.